Navier-Stokes equations paradox. Issue 1 (August 2021) - Ramm, Alexander G.
Abstract : It is proved that if the Navier-Stokes problem is considered in ℝ 3, then the initial velocity has to be zero. This is the paradox. The consequences of this paradox are: a) The NSP is contradictory physically and mathematically; it is not a correct formulation of the problem of motion of the incompressible viscous fluid. b) The solution to the NSP does not exist on [0, ∞). This solves one of the millennium problems.